Examining the nature of the comorbidity between pediatric attention deficit/hyperactivity disorder and post‐traumatic stress disorder. (18th September 2012) - Biederman, J.; Petty, C. R.; Spencer, T. J.; Woodworth, K. Y.; Bhide, P.; Zhu, J.; Faraone, S. V.
<x xml:space="preserve">Abstract</x> Biederman J, Petty CR, Spencer TJ, Woodworth KY, Bhide P, Zhu J, Faraone SV. Examining the nature of the comorbidity between pediatric attention deficit/hyperactivity disorder and post‐traumatic stress disorder. Objective: This study sought to address the link between attention deficit/hyperactivity disorder (ADHD) and post‐traumatic stress disorder (PTSD) in youth by providing a comprehensive comparison of clinical correlates of ADHD subjects with and without PTSD across multiple non‐overlapping domains of functioning and familial patterns of transmission. Method: Participants were 271 youths with ADHD and 230 controls without ADHD of both sexes along with their siblings. Participants completed a large battery of measures designed to assess psychiatric comorbidity, psychosocial, educational, and cognitive parameters. Results: Post‐traumatic stress disorder was significantly higher in ADHD probands vs. controls (5.2% vs. 1.7%, χ2(1) = 4.36, P = 0.04). Irrespective of the comorbidity with PTSD, ADHD subjects had similar ages at onset of ADHD, similar type and mean number of ADHD symptoms, and similar ADHD‐associated impairments. PTSD in ADHD probands was significantly associated with a higher risk of psychiatric hospitalization, school impairment, poorer social functioning and higher prevalences of mood, conduct disorder, and anxiety disorders. The mean onset of PTSD (12.6 years) was significantly later than that of ADHD and comorbid disorders (all P < 0.05). Siblings of ADHD and ADHD + PTSD probands had higher prevalences of ADHD vs. siblings of controls (35% vs. 18%, z = 4.00, P < 0.001 and 67% vs. 18%, z = 4.02, P < 0.001 respectively) and siblings of ADHD+PTSD probands had a significantly higher prevalence of PTSD compared with the siblings of ADHD and control probands (20% vs. 3% and 3%, z = 2.99, P = 0.003 and z = 2.07, P = 0.04 respectively). Conclusion: Findings indicate that the comorbidity with PTSD in ADHD leads to greater clinical severity as regards psychiatric comorbidity and psychosocial dysfunction. ADHD is equally familial in the presence of PTSD in the proband indicating that their co‐occurrence is not owing to diagnostic error.